CHARACTERIZATION OF THERMAL PRECIPITATOR IN SMOKE COLLECTOR BY USING PARTICLE COUNTER - Imansyah Ibnu Hakim; Bambang Suryawan; I Made Kartika D; Nandy Putra; Cahyo Setyo Wibowo (Testing Center for Oil and Gas LEMIGAS, 2012)
Air pollution in major cities in many countries has reaching a very concerning level. One of thecause of air pollution is pollution caused by smoke aerosol. Smoke aerosols that has an averageparticle diameter of 0.1 μm – 1 μm can be found in cigarette smoke, diesel vehicle fume, industrialfume and many else. This condition will be worsen by the increase in the number of smokers, motorvehicles and industry. Therefore we need to pursue the control method for that kind of air pollution.In the literature study, it’s found that the cleaning method of air fi ltration for fi ne particle withdimension of 0.01 – 5 μm are by using thermal precipitator. Thermal precipitator is one method ofair fi ltration based on thermophoretic force, which is if there is a temperature difference betweentwo plates, it will cause the force that will push the particles between the two plates toward theplate that has lower temperature. In the effort to help control and reduce the air pollution, for thisstudy we made a thermal precipitator test equipment to deposit the particles in the air with the useof thermophoretic force. That force is the force applied to the particles that suspended in the fl uidfl ow. The temperature difference between two plates is set at ΔT=5, 10, 15, and 20oC. This studyutilized gas sensors to observe the characterization of thermal precipitator. From the experimentand analysis can be concluded that thermal precipitator can be applied as a smoke collector.